Ultrasmall bimetallic Cu/ZnOx nanoparticles encapsulated in UiO-66 by deposition–precipitation method for CO2 hydrogenation to methanol. (15th September 2022) - Yu, Jun; Chen, Guoqing; Guo, Qiangsheng; Guo, Xiaoming; Da Costa, Patrick; Mao, Dongsen
Graphical abstract: Highlights: Cu/ZnOx particles were encapsulated in UiO-66 by deposition–precipitation method. Both of metal loading and Cu/Zn mole ratio can regulate the Cu-Zn interaction. The amount of Cu/ZnOx interfaces is related to the methanol synthesis performance. Abstract: A series of Cu-Zn catalysts encapsulated by Zr-based metal–organic frameworks (UiO-66) with various metal loadings and Cu/Zn mole ratios were prepared by the deposition–precipitation method, and the catalytic activities were investigated by CO2 hydrogenation to methanol. The results showed that Cu-Zn@UiO-66 catalyst with Cu-Zn loading of 35 wt% and Cu/Zn mole ratio of 2.5 had the best catalytic activity. At 240 °C and 3 MPa, this catalyst gave the excellent catalytic activity with the highest methanol yield of 9.1%, and showed good reaction stability during 100-hour catalytic test. The catalysts were characterized by N2 -sorption, XRD, TEM, XPS, H2 -TPR and CO2 -TPD. Such excellent performance benefits from the ultrasmall nanoparticles (NPs) and abundant Cu/ZnOx interfaces confined in the UiO-66, and the strong interaction between Cu and ZnO promotes the CO2 conversion and methanol synthesis.